Two-Dimensional Visualization of Solid Expansion Using Spyder as a Physics Learning Medium in Secondary Schools - Farel Adya Falefi; Himawan Puranta (Kasuari: Physics Education Journal (KPEJ), 2026)
Physics education in secondary schools still faces several obstacles, particularly in understanding the concepts of temperature and heat, one of which is the expansion of solids. The main problem students face is difficulty visualizing how the size of solids changes as temperatures rise, so learning tends to consist only of memorizing formulas without a deep understanding. This study aims to explain the use of two-dimensional (2D) solid expansion graphs using Python-based Spyder software as a medium for physics learning. The method used is simulation and mathematical modeling of area expansion based on physical equations, with the results displayed as graphs. The simulation shows a linear relationship between temperature changes and the area of a solid object, in accordance with the area-expansion theory . Graph visualization helps students understand how temperature affects changes in object size and how expansion varies across materials, depending on their respective coefficients of thermal expansion. In addition, Spyder encourages active student participation, improves critical thinking skills, and provides a basic introduction to programming. Thus, the use of solid expansion graphs in Spyder can be an effective, interactive, and relevant alternative learning medium to improve the quality of physics learning at the secondary school level.